The level of service ability in the final four 2019 pro league men's players - Kalvin Aprilian; Nur Ahmad Muharram; Wing Prasetya Kurniawan (Universitas Sebelas Maret, 2022)
This research is based on observations in the form of an analysis of the level of difficulty of the service performed by each player depending on the type of service used, such as floating service, jump float, and jumping service top spin. A good service is the direction of the ball to the empty side of the field or between two players. It is intended for when the opponent receives a service in a moving position or creates a misunderstanding between two players because the ball is between the two players. The service above is the type of service that is often done by players from the beginner level to the professional level. However, there are still many professional players who competed in the 2019 proliga, the first round of the men's sector, not all of them know what type of service is most productive. In accordance with the problem formulation, the purpose of this research is to determine the level of ability of floating service, jump float service and jumping service top spin in the final four proliga 2019 men's volleyball. This study uses a survey method with data collection techniques using observations (observations) by judges and document analysis (video). The conclusion from the research that has been done is that the results of each team regarding service ability are the ability of floating service of 8.88 and if presented in percentage form, it is 11.27%, Jump float service ability is 33.63 and if presented in percentage form, it is 42, 65%, the ability to jump service top spin is 36.33 and if it is presented as a percentage, it is 46.08%. From the discussion, it was concluded that the level of service ability in the 2019 proliga men's volleyball final according to the results of observations and observations through video observations, it was concluded that the Jumping service Top Spin had the highest ability value compared to the service float and jump float of 46.08%.